Therapeutics for neurodegenerative diseases by targeting the gut microbiome: from bench to bedside - Yuan-Yuan Ma; Xin Li; Jin-Tai Yu; Yan-Jiang Wang (Translational Neurodegeneration, 2024)
Abstract The aetiologies and origins of neurodegenerative diseases, such as Alzheimer’s disease (AD), Parkinson’s disease (PD), amyotrophic lateral sclerosis (ALS) and Huntington’s disease (HD), are complex and multifaceted. A growing body of evidence suggests that the gut microbiome plays crucial roles in the development and progression of neurodegenerative diseases. Clinicians have come to realize that therapeutics targeting the gut microbiome have the potential to halt the progression of neurodegenerative diseases. This narrative review examines the alterations in the gut microbiome in AD, PD, ALS and HD, highlighting the close relationship between the gut microbiome and the brain in neurodegenerative diseases. Processes that mediate the gut microbiome–brain communication in neurodegenerative diseases, including the immunological, vagus nerve and circulatory pathways, are evaluated. Furthermore, we summarize potential therapeutics for neurodegenerative diseases that modify the gut microbiome and its metabolites, including diets, probiotics and prebiotics, microbial metabolites, antibacterials and faecal microbiome transplantation. Finally, current challenges and future directions are discussed.